MARKETPLACE’S PERCEIVED EASE OF USE, HARGA DAN PROMOSI TERHADAP MINAT BELI ULANG KONSUMEN - Ema Santona; Sudaryanto Sudaryanto; Mochammad Farid Afandi (BISMA: Jurnal Bisnis dan Manajemen, 2021)
This study aims to examine the effect of perceived ease of use, price, and promotion on the repurchase interest of Tokopedia consumers. The sampling technique used in this study was purposive sampling, a sample collection technique with specific considerations. The number of samples was 120 respondents. The types of data used were qualitative data obtained through various kinds of data collection techniques and quantitative data, which is in numbers. Questionnaires were used as data collection instruments to support this research. The data collected was then analyzed by applying multiple linear regression analysis methods. The results of this study indicate that perceived ease of use, price, and promotion have a significant effect on repurchase intention.